2021
DOI: 10.3389/fcvm.2021.669245
|View full text |Cite
|
Sign up to set email alerts
|

Association of Carotid Intima Media Thickness With Metabolic Syndrome Among Low-Income Middle-Aged and Elderly Chinese: A Population-Based Cross-Sectional Study

Abstract: Background: We aimed to evaluate the relationship between metabolic syndrome (MetS) including its components and carotid intima media thickness (CIMT) in a low-income Chinese population aged ≥45 years.Methods: The participants underwent a general health screening and B-mode carotid ultrasonography that measured CIMT. The diagnosis of MetS and its components was based on the modified International Diabetes Federation Criteria for the Asian Population. The univariate and multivariable linear regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…44 Obesity is associated with a chronic inflammatory process characterised by an increase in different proinflammatory biomarkers, which may mediate all stages of atherogenesis, including the beginning, acceleration, and development of atherosclerotic lesions. 45 According to the Brazilian Longitudinal Study of Adult Health, for each 1-cm rise in WC, CIMT increased by 0.08 mm ( = 0.08; 95% CI, 0.04-0.11; P 0.0001). 46 hsCRP levels were also considerably higher in a subset of patients with CVD, hypertension, diabetes, and visceral obesity compared to a subset of people without such diseases.…”
Section: Discussionmentioning
confidence: 97%
“…44 Obesity is associated with a chronic inflammatory process characterised by an increase in different proinflammatory biomarkers, which may mediate all stages of atherogenesis, including the beginning, acceleration, and development of atherosclerotic lesions. 45 According to the Brazilian Longitudinal Study of Adult Health, for each 1-cm rise in WC, CIMT increased by 0.08 mm ( = 0.08; 95% CI, 0.04-0.11; P 0.0001). 46 hsCRP levels were also considerably higher in a subset of patients with CVD, hypertension, diabetes, and visceral obesity compared to a subset of people without such diseases.…”
Section: Discussionmentioning
confidence: 97%
“…NLR measurement has a high effectiveness-cost ratio and good reliability due to its lower variability by treatments ( 5 , 12 , 16 ). In addition, MetS is a common clinical condition in the elderly people ( 17 19 ). Studies have shown that elderly patients with MetS were vulnerable to increased coronary atherosclerosis-related events and cardiac mortality ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%